Comparison Towards Different Methods of Software Debugging - Tajimalela, Akwan Cakra; Suryahadi, Ramandha Putra; Alfadilla, Rizka; Syawanodya, Indira; Tawakal, Iqbal (Universitas Pendidikan Indonesia (UPI), 2024)
To ensure that software works as expected, debugging is essential. This article discusses several types of debugging, focusing on Visual Studio Code Debugger, print statement debugging, and static code analysis. Each method is demonstrated through a simple yet comprehensive program that determines whether a selected number is a prime number. We conclude that the Visual Studio Code Debugger offers powerful features but requires prior experience with Visual Studio Code. Print statement debugging is straightforward but can become cumbersome in more complex programs. Static code analysis, particularly with ESLint, does not directly uncover